CXCR3+ T Follicular Helper Cells Induced by Co-Administration of RTS,S/AS01B and Viral-Vectored Vaccines Are Associated With Reduced Immunogenicity and Efficacy Against Malaria - Bowyer, Georgina; Grobbelaar, Amy; Rampling, Tommy; Venkatraman, Navin; Morelle, Danielle; Ballou, Ripley W.; Hill, Adrian V. S.; Ewer, Katie J. (Frontiers in Immunology, 2018)
A malaria vaccine strategy targeting multiple lifecycle stages may be required to achieve a high level of efficacy. In two Phase IIa clinical trials we tested immunogenicity and efficacy of RTS,S/AS01B administered alone, in a staggered regimen with viral vectored vaccines or co-administered with viral vectored vaccines. RTS,S/AS01B induces high titres of antibody against sporozoites and viral vectored vaccines ChAd63 ME-TRAP and MVA ME-TRAP induce potent T cell responses against infected hepatocytes. By combining these two strategies we aimed to improve efficacy by inducing immune responses targeting multiple parasite antigens. Vaccination with RTS,S/AS01B alone or in a staggered regimen with viral vectors produced strong immune responses and demonstrated high levels of protection against controlled human malaria infection (CHMI). However, concomitant administration of these vaccines significantly reduced humoral immunogenicity and protective efficacy. Strong Th1-biased cytokine responses induced by MVA ME-TRAP were associated with a skew in circulating T follicular helper cells towards a CXCR3+ phenotype and a reduction in antibody quantity and quality. This study illustrates that while a multistage-targeting vaccine strategy could provide high-level efficacy, the regimen design will require careful optimisation.